Revelation of native vegetation succession on tropical coral island ecological restoration - Zhiyuan Shi; Jianting Cao; Ziyi Wang; Lin Zhang; Shasha Niu; Wenqing Wang (Ecosphere)
Abstract Tropical coral island vegetation poses formidable challenges, particularly in elucidating the determinants of vegetation species richness. In response, our study compared the differences in plant species biodiversity and soil physicochemical properties on seven adjacent coral islands at different stages of vegetation succession, from bare land to 100% vegetation coverage in the South China Sea, all of which were less than 0.3 km2. Contrary to the established island ecological theories, our results indicated that soil nutrients significantly govern the species diversity of tropical coral islands. However, the timing of soil development, island area, distance from larger islands, and island altitude were not significantly correlated. Cluster analysis showed that the diverse islands of Qilianyu Island (Seven Sisters) represent distinct stages of tropical coral island succession: pioneer vegetation, shrub and grass communities, and coral island forest vegetation. As island vegetation underwent succession, plant species increased from 6 to 57, and organic carbon, total nitrogen, and available phosphorus content significantly increased, accompanied by increasing salinity and decreasing pH. Our findings revealed a nested structure in the vegetation of tropical coral islands, primarily dominated by environmental filtering on a small scale, at least on Qilianyu Island. This indicates that the restoration of damaged island vegetation can begin with soil rehabilitation. We contend that improving soil nutrient conditions and development status contribute to the establishment of island vegetation, with careful consideration of interspecific combinations that expedite the restoration process on tropical coral islands. This study addresses the lack of clarity surrounding the determinants of vegetation species richness on tropical coral islands, thus providing a novel perspective grounded in soil nutrient‐driven succession.